Street Smut: Gender, Media, and the Legal Power Dynamics of Street Harassment, or Hey Sexy and Other Verbal Ejaculations - Laniya, Olatokumbo Olukemi (Columbia Journal of Gender and Law, 2005)
Unfortunately, these women’s experiences are not rare. Indeed, such astonishing encounters occur in the daily lives of women throughout the world. Rarely is it the case that a woman in a public space is not confronted with unsolicited comments and gestures of a sexual tone by men unknown to her. Yet, it is precisely the ubiquity of this phenomenon that distills its perceived effects on women and on society as a whole. Most men view the occurrence as harmless and even desired by women, while most women resign themselves to the inevitability of the acts and the absence of a vehicle to remedy such harm. Notwithstanding these somewhat discouraging facts, there is hope for a remedy to this problem. Those who fight against the sexual harassment of women in public places may find encouragement in the advancements made towards the recognition and redress of other harms that largely affect women, such as sexual harassment in the workplace. The notion of sexual harassment in the workplace was unknown fifty years ago, but is now recognized as a valid harm to women and to society. Great strides have been made in this arena, and women now have legally cognizable claims under Title VII and state non-discrimination laws. Further, this type of sexual harassment is socially condemned; it is no longer “what bosses do,” but carries with it a condemnation that reflects the changing ethical judgments of society. Thus, progress has been made, and this advancement helps to fortify the convictions of those who currently fight against the harassment of women in public places and other forms of sexual harassment that are not yet recognized as real injuries to women.